Cardiovascular health in pediatric patients with X-linked hypophosphatemia under two years of burosumab therapy - Brener, Avivit; Cleper, Roxana; Baruch, Guy; Rothschild, Ehud; Yackobovitch-Gavan, Michal; Beer, Gil; Zeitlin, Leonid; Kapusta, Livia (Frontiers in Endocrinology, 2024)
Introduction: X-linked hypophosphatemia (XLH) is caused by an inactivating mutation in the phosphate-regulating endopeptidase X-linked (PHEX) gene whose defective product fails to control phosphatonin fibroblast growth factor 23 (FGF23) serum levels. Although elevated FGF23 levels have been linked with detrimental cardiac effects, the cardiologic outcomes in XLH patients have been subject to debate. Our study aimed to evaluate the prevalence and severity of cardiovascular morbidity in pediatric XLH patients before, during, and after a 2year treatment period with burosumab, a recombinant anti-FGF23 antibody Methods: This prospective observational study was conducted in a tertiary medical center, and included 13 individuals with XLH (age range 0.6-16.2 years) who received burosumab every 2 weeks. Clinical assessment at treatment initiation and after .5, 1, and 2 years of uninterrupted treatment included anthropometric measurements and cardiologic evaluations (blood pressure [BP], electrocardiogram, conventional echocardiography, and myocardial strain imaging).The linear growth of all patients improved significantly (mean height z-score: from -1.70±0.80 to -0.96±1.08, P=0.03). Other favorable effects were decline in overweight/obesity rates (from 46.2% to 23.1%) and decreased rates of elevated BP (systolic BP from 38.5% to 15.4%; diastolic BP from 38.5% to 23.1%). Electrocardiograms revealed no significant abnormality throughout the study period. Cardiac dimensions and myocardial strain parameters were within the normative range for age at baseline and remained unchanged during the study period.Cardiologic evaluations provided reassurance that 2 years of burosumab therapy did not cause cardiac morbidity. The beneficial effect of this treatment was a reduction in cardiovascular risk factors, as evidenced by the lower prevalence of both overweight/obesity and elevated BP.